Modelling of mobility mechanism for Motorized Adjustable Vertical Platform (MAVeP) - Abd Mutalib, Mohd Azri; Zainul Azlan, Norsinnira; Mahmood, Iskandar Al-Thani (Institute of Electrical and Electronics Engineers Inc., 2019)
During the thermal vacuum, acoustic and vibration test procedure before launching, a satellite needs to be transported from one test area to another area using a mobile platform. To cater the demand, a special platform called Motorized Adjustable Vertical Platform (MAVeP) has been designed and assembled to ensure a smooth transfer operation and to reduce the handling risk that may jeopardize the satellite. This platform is able to move around and equipped with a height adjustable mechanism to elevate the satellite. This paper focuses on the design and modelling of MAVeP mobility. High accuracy and repeatability parking is an important criteria in the mechanical and electrical design. Kinematics and dynamic model of MAVeP mobility is described in this paper and verified experimentally. The result show that the kinematic and dynamic modelling errors are 0.08m respectively and MAVeP is able to move in a confined environment and desired.